2015
DOI: 10.1016/j.ijrobp.2015.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice Claims in Radiation Oncology: A Population-Based Study 1985-2012

Abstract: Purpose/Objective(s) To determine trends in radiation oncology malpractice claims and expenses during the last 28 years and compare malpractice claims between radiation oncology and other specialties. Methods and Materials We performed a retrospective analysis of closed malpractice claims filed from 1985 to 2012 collected by a nationwide medical liability insurance trade association. We analyzed characteristics and trends among closed claims, indemnity payments (payments to plaintiff), and litigation expense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
3
2
Order By: Relevance
“…Thus, our results also raise a question as to whether physicians are more concerned about malpractice claims now than they were 16 years ago. The data from malpractice claims are conflicting, as some studies show an increasing amount of malpractice claims, while in others, there is a clear decrease 34 35. In contrast to our results, the law appeared to play a limited role in EOL medical decision-making with doctors prioritising patient-related clinical and ethical considerations in a recent study from Australia 36.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, our results also raise a question as to whether physicians are more concerned about malpractice claims now than they were 16 years ago. The data from malpractice claims are conflicting, as some studies show an increasing amount of malpractice claims, while in others, there is a clear decrease 34 35. In contrast to our results, the law appeared to play a limited role in EOL medical decision-making with doctors prioritising patient-related clinical and ethical considerations in a recent study from Australia 36.…”
Section: Discussioncontrasting
confidence: 99%
“…The data from malpractice claims is conflicting, as some studies show an increasing amount of malpractice claims, while in others there is a clear decrease. [34,35] In contrast to our results, the law appeared to play a limited role in end-of-life medical decision-making with doctors prioritizing patient-related clinical and ethical considerations in a recent study from Australia. [36] On the other hand, that study is partly in line with our study, as ethical values were also considered to be highly influential by our responders.…”
Section: Factors Associated With Physicians' Decisionscontrasting
confidence: 99%
“…9 Medical liability insurance is a type of insurance that may protect physicians against claims of medical negligence. 10 Markets of medical liability insurance have occasionally experienced crisis, such as in the mid-1970s, mid-1980s, and early 2000s. 11 Since the 2000s, the medical liability insurance markets have been moderately stable.…”
Section: Introductionmentioning
confidence: 99%
“…Improper performance claims also carried the highest average indemnity payment among the most frequent alleged errors. Reported error rates in radiation therapy are low (fewer than 2% of treatments) 2329 , and studies suggest these events are decreasing over time 30,31 along with malpractice claims against radiation oncologists 13 . When errors do occur, most relate to human error or human-software interface 25,28,32 , especially among incidents with the potential to cause serious clinical harm 31 .…”
Section: Discussionmentioning
confidence: 99%
“…An important part of reducing legal risk to physicians is to understand why people sue 12 . A recent population-based study of malpractice claims involving radiation oncologists found that these claims are not common and have declined in recent years 13 . However, this study also found that indemnity payments in radiation oncology are large relative to other specialties, and the risk of being sued is relatively high compared to other nonsurgical specialties.…”
Section: Introductionmentioning
confidence: 99%